The Use of Mnemonic Technique in Increasing Students’ English Vocabulary Mastery - Ummul Husnul Auliya; Nurdin, Nurdin; Afifah, Afifah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2024)
Acquiring a sufficient vocabulary in English can be a formidable obstacle, which in turn affects one's proficiency in listening, speaking, reading, and writing. Students frequently encounter difficulties in comprehending word meanings. In order to tackle this issue, multiple strategies are utilized to improve one's command of vocabulary, one of which is the Mnemonic Technique. This study examines the efficacy of the Mnemonic Technique in enhancing vocabulary acquisition among tenth-grade students at SMKS Muhammadiyah Marawola. The data for this study were acquired through field notes, observation sheets, and pre-test and post-tests as part of a Classroom Action Research project. The Mnemonic Technique, specifically the acrostic approach, was employed to enhance memory by constructing sentences. The study comprised two iterations, with each iteration encompassing preparation, execution, observation, and reflection stages. The results demonstrated a noteworthy enhancement in the students' proficiency in language. During cycle I, the average pre-test score was 65.87, which subsequently rose to 73.87 in the post-test. During cycle II, the average post-test score showed a further improvement to 89.87. The proportion of pupils achieving the passing grade increased from 75% in cycle I to 87.5% in cycle II. In conclusion, the Mnemonic Technique has been shown to be beneficial in improving students' vocabulary, increasing their level of engagement, fostering creativity, and leading to higher learning outcomes.